2019
DOI: 10.1177/1040638719843577
|View full text |Cite
|
Sign up to set email alerts
|

A two-year prospective study of small poultry flocks in Ontario, Canada, part 1: prevalence of viral and bacterial pathogens

Abstract: In Ontario, within the past few years, there has been a marked increase in the number of non-commercial poultry flocks (referred to as "small flocks"). Small poultry flocks may act as a reservoir of avian and zoonotic pathogens, given the flocks' limited access to veterinary services, inadequate biosecurity practices, and increased risk of contact with wild birds. Despite these potential risks, there is a scarcity of data concerning the prevalence of poultry and zoonotic pathogens among these flocks. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 34 publications
2
40
1
1
Order By: Relevance
“…Nonetheless, the presence of AMR in Salmonella in small flocks is concerning because of the risk that resistant salmonellae pose in human cases with bacteremia or a compromised immune system. Although the frequency of Salmonella enterica was very low in our study [26], and many of the Salmonella isolates were pan-susceptible, some were resistant to streptomycin alone, or to streptomycin, sulfisoxazole, trimethoprim-sulfamethoxazole, and tetracycline. Our findings agree with a recent study that evaluated AMR in Salmonella isolated from small flock cases at the California Animal Health and Food Safety Laboratory System, and found resistance to streptomycin, sulfonamides, and tetracycline [34].…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Nonetheless, the presence of AMR in Salmonella in small flocks is concerning because of the risk that resistant salmonellae pose in human cases with bacteremia or a compromised immune system. Although the frequency of Salmonella enterica was very low in our study [26], and many of the Salmonella isolates were pan-susceptible, some were resistant to streptomycin alone, or to streptomycin, sulfisoxazole, trimethoprim-sulfamethoxazole, and tetracycline. Our findings agree with a recent study that evaluated AMR in Salmonella isolated from small flock cases at the California Animal Health and Food Safety Laboratory System, and found resistance to streptomycin, sulfonamides, and tetracycline [34].…”
Section: Discussioncontrasting
confidence: 59%
“…Limitations of this study include a sampling bias, as most submissions came from southwestern and eastern Ontario, which might have been the consequence of the geographic proximity to the diagnostic laboratories in Guelph and Kemptville, respectively [26]. Also, small flocks were not randomly selected, and our study included only owners who had a flock veterinarian, as ciprofloxacin; NAL = nalidixic acid; TET = tetracycline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Details concerning the study design are reported in part 1 of the series. 2 Information on the bird species, age, sex, flock size, location, date of submission, and clinical history was collected as part of the postmortem submission. A routine postmortem examination was performed on all birds from each submission, including ancillary tests to determine the cause of morbidity or mortality.…”
Section: Methodsmentioning
confidence: 99%